Assessment of the impact of industry factors on the pricing of autoclave aerated concrete products in Ukraine in 2011-2021 - Skrypnyk, Olha; Skrypnyk, Andrii (Ways to Improve Construction Efficiency, 2022)
The article assesses the impact of industry factors on the pricing of autoclaved aerated concrete (AAC) products in Ukraine in 2011-2021. The authors have identified the main industry factors of price formation on the Ukrainian aerated concrete market from the supply and demand sides. The authors also conducted a stochastic factor analysis of the dependence of prices for AGB on the prices of key raw materials for its production (M-400 cement and river sand). The analysis proved a high level of correlation between prices for AGB and key raw materials, which is due to the significant material intensity of production. An extremely high degree of correlation was also established between prices for the raw materials themselves, but the analysis showed that their prices can change in different directions, which allows them to be used in multifactor forecasting models. The authors conducted a stochastic analysis of raw material prices from the influence of macroeconomic factors. He demonstrated that the volume of construction work has the least impact on the prices of raw construction materials, which makes them unsuitable for forecasting raw material prices. Average wages, average prices based on the CPI, and nominal GDP have a significant impact on raw material prices, as they affect both cost and demand. The exchange rate has a small impact, since there are no import components in the cost of raw materials. Based on factor analysis, single-factor regression models were constructed that can be used to forecast cement and sand prices, which makes it possible to indirectly estimate future cost and prices for AGB. Comparative analysis showed that in 2011–2021. prices for AGB grew more slowly than its cost, which led to a decrease in production profitability and the shutdown of some enterprises in the industry. This confirms the need to develop comprehensive mechanisms for regulating pricing for AGB as a socially significant production commodity. The results of the study can be used by manufacturers, developers and state regulatory authorities to improve the efficiency of management decisions and form a reasonable pricing policy for AGB.